New Stability Results of Multiplicative Inverse Quartic Functional Equations - et. al., Beri V. Senthil Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this investigation is to introduce different forms of multiplicative inverse functional equations, to solve them and to establish the stability results of them in the framework of matrix normed spaces. A suitable counter-example is also provided to prove the instability of the results for a singular case. The applications of the equations dealt in this study are discussed with the fluid resistances of blood vessels and also an important concept in Raman spectroscopy. 2010 Mathematics Subject Classification. 39B82, 39B72.